Moderate Character Education in Sasak Cultural Institutions: An Islamic Education Perspective - Baiq Mulianah (UIN Mataram, 2024)
This study explores moderate character education within the cultural institutions of the Sasak community from the perspective of Islamic Religious Education. In Sasak society, the values of religious moderation have long been embedded through various traditions and social institutions that reflect attitudes of tolerance, balance (wasatiyyah), and inclusivity. Islamic education, particularly within pesantren and madrasah, plays a strategic role in strengthening the moderate character within society. This study employs a qualitative approach, utilizing literature reviews and observations of local cultural practices that contribute to fostering a moderate religious mindset. The findings indicate that moderate character education within the Sasak community is reflected in traditions such as begibung, nyongkolan, and customary law practices (awig-awig), which instill values of solidarity and social harmony. Furthermore, the role of Tuan Guru in educating santri about Islam as rahmatan lil ‘alamin (a mercy to all creation) is crucial in maintaining a balance between Islamic teachings and local wisdom. However, contemporary challenges such as uncontrolled digital information flow and the rise of extremist discourse on social media necessitate adaptive strategies in Islamic education. Therefore, strengthening moderation-based curricula, leveraging technology for Islamic education and dakwah, and fostering collaboration between pesantren and higher education institutions are essential strategies to sustain moderation values in the digital era. In conclusion, moderate character education within Sasak cultural institutions represents an integration of Islam and local wisdom that fosters an inclusive and harmonious society. Synergy between Islamic educational institutions, religious scholars (ulama), and the government is crucial in reinforcing an education system based on moderation values to address the challenges posed by globalization and technological advancements. Abstrak: Penelitian ini membahas pendidikan karakter moderasi dalam pranata budaya Sasak dari perspektif Pendidikan Agama Islam. Dalam masyarakat Sasak, nilai-nilai moderasi beragama telah lama tertanam melalui berbagai tradisi dan pranata sosial yang mencerminkan sikap toleransi, keseimbangan (wasatiyyah), dan inklusivitas. Pendidikan Islam, khususnya dalam lingkungan pesantren dan madrasah, memiliki peran strategis dalam memperkuat karakter moderasi di tengah masyarakat. Kajian ini menggunakan pendekatan kualitatif dengan metode studi pustaka dan observasi terhadap praktik-praktik budaya lokal yang berkontribusi dalam membangun sikap moderat dalam beragama. Hasil penelitian menunjukkan bahwa pendidikan karakter moderasi di masyarakat Sasak terefleksikan dalam tradisi begibung, nyongkolan, dan praktik hukum adat (awig-awig), yang mengajarkan nilai kebersamaan dan harmoni sosial. Selain itu, peran Tuan Guru dalam mendidik santri tentang Islam yang rahmatan lil ‘alamin menjadi kunci dalam menjaga keseimbangan antara ajaran Islam dan kearifan budaya lokal. Namun, tantangan modern seperti arus informasi digital yang tidak terkontrol dan meningkatnya wacana ekstremisme di media sosial mengharuskan adaptasi dalam pendidikan Islam. Oleh karena itu, penguatan kurikulum berbasis moderasi, pemanfaatan teknologi dalam dakwah dan pembelajaran, serta kolaborasi antara pesantren dan institusi pendidikan tinggi menjadi strategi utama dalam menjaga nilai-nilai moderasi di era digital. Kesimpulannya, pendidikan karakter moderasi dalam budaya Sasak merupakan model integrasi antara Islam dan kearifan lokal yang mampu membentuk masyarakat yang inklusif dan harmonis. Sinergi antara lembaga pendidikan Islam, ulama, dan pemerintah sangat diperlukan untuk memperkuat sistem pendidikan berbasis nilai-nilai moderasi guna menghadapi tantangan globalisasi dan teknologi. Keywords: Character education, religious moderation, Sasak cultural institutions, Islamic education, digital transformation.